Analisis Heat Stress saat Kondisi El – Niño, La – Niña, dan Netral di Wilayah Jakarta dan Sekitarnya Periode 1993 – 2018 - Muhamad Fajri Zulkifar; Santy Wulandari; Rista Hernandi Virgianto (Buletin GAW Bariri, 2020)
Jakarta and its surroundings areas that have high surface temperatures due to high total CO2 emissions. High CO2 emissions will cause surface temperatures to increase due to the phenomenon of greenhouse gases. An increase in temperature will also have an impact on increasing heat strs which will be dangerous if no steps are taken for prevention. The El Niño – Southern Oscillation (ENSO) factor is also considered influential in terms of the value of heat stress. Calculating heat stress in Jakarta and surrounding areas can be done by the Wet-Bulb Globe Temperature Index (WBGT) method. Data was obtained from six station points in Jakarta and surrounding areas in 1993 – 2018 consisting of daily air temperature and humidity and using Oceanic Nino Index (ONI) data to determine the ENSO period. The results show that the highest WBGT were identified in four regions, Tanjung priok, Kemayoran, Cengkareng and South Tangerang with ISBB values ​​of 30 – 32.5 (the heat stress increases to dangerous levels), while for the other two, Curug and Dramaga Bogor have WBGT values at 28.5 – 30 (heat stress increases). The most dangerous WBGT category was in Tanjung priok in April during El – Niño with 71% (58) days were in the dangerous category, while the WBGT category had the least heat stress at Dramaga in August when it was neutral with 17.7% (66) days were in the no heat stress category. When El-Niño ISBB was higher than when it is neutral and La-Niña and has higher minimum and maximum extreme values than when it is neutral and La – Niña.